Editorial - López González, Álvaro Santiago (Universidad Nacional Autónoma de Nicaragua, Managua. Centro Universitario Regional de Carazo, 2018)
Editorial, Revista Torreón Universitario, Vol. 6 Núm. 17 (2017)